THE INFLUENCE OF HEAT TREATMENT WITH THE LIQUID PHASE ON FORMATION OF A MICROSTRUCTURE OF EUTECTIC Al-Si-ALLOY - A. Anikin; S. Belyaev; V. Zhereb; V. Anikina; T. Gil’manshina; A. Semusheva (Литьë и металлургия, 2015)
The effect of heat treatment on the structure of the eutectic Al-Si-alloy, a theoretical substantiation process based on thermal analyzer and cooked microstructures was presented in this paper.